Stakeholder Dialogue in PT Telkom Indonesia's Corporate Social Responsibility Program: (Case Study on Telkom Regional 3 West Java's MSME Development Activities) - Firdaus, Indi Aires; Mukhlisiana, Lusy (PT Mattawang Mediatama Solution, 2024)
Stakeholder dialogue is an important element because it allows constructive participation with parties involved in Corporate Social Responsibility. PT Telkom Indonesia, which runs a Micro, Small and Medium Enterprises development program as CSR, builds dialogue with business actors to jointly make the program a success. This study starts from problems that need to be communicated between the two parties, such as conveying complaints and aspirations. Thus, this study aims to examine stakeholder dialogue in MSME development as a CSR activity of Telkom Indonesia. This study uses a qualitative approach with a case study method. The results of the study show that stakeholder dialogue is carried out both internally and externally. The stakeholder dialogue that occurs is in the form of interaction through social media channels for coordination, as well as conducting company visits to fostered partners offline. In addition, dialogue occurs in monitoring and evaluation activities where the company discusses feedback provided by fostered partners as external parties.